DESIGN OF COLD STORAGE WITH 3 TONS OF CHICKEN MEAT PRODUCTS - Nia Nuraeni Suryaman; Udin Komarudin (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The population of Indonesia has increased every year. This is the cause of the search for food needs, one of which is the need for chicken meat. Chicken farmers need to design so that the chicken meat products produced have good quality when consumed by the public. Apart from handling when the chickens are still alive, the quality of chicken that has been slaughtered for consumption also needs to be maintained. The refrigeration field is currently widely used for personal or commercial needs, including for the food industry. One of the applications in the refrigeration sector is cold storage. Due to the extensive research on cold storage, this research will only design a cold storage to store 3 tons of chicken meat. The purpose of this research is to design cold storage, select and identify refrigeration equipment and refrigeration control used in this cold storage design. In this study, the steam compression system uses a multi rack compressor. Cold storage is only to maintain the temperature of the chicken meat, not to cool the chicken meat. The result of this research is the total capacity of this design equipment is 5.4 kW. This cold storage uses 3 compressors, where 1 compressor is a backup compressor. Each compressor has a capacity of 2.7 kW. Equipment selection using Bitzer, Guntner and Danfoss software.